2018
DOI: 10.1002/sd.1740
|View full text |Cite
|
Sign up to set email alerts
|

Gathering society's opinion of the sustainable management and economic value of the coastal zone

Abstract: This study explores people's perceptions of marine ecosystem services and sustainable coastal zone management. More specifically, it investigates the relationship between respondents' attitudes and motives for placing economic value on the coastal zone, expressing their intention to pay for coastal zone quality improvement. Primary data were obtained from a sample of 468 people living on the coastline of the Pagasitikos Gulf. Respondents' attitude was measured using questions that include issues related to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 72 publications
1
4
0
Order By: Relevance
“…We found that women are more concerned with the environment than men. This result is consistent with other research findings in different geographical contexts, such as Greece, the US, India, and Brazil, demonstrating that women care more about the environment than men and score higher on the NEP scale [17,[78][79][80][81]. This finding can be attributed to gender roles, societal expectations, and women's perceived responsibility for household and community well-being.…”
Section: Discussionsupporting
confidence: 91%
“…We found that women are more concerned with the environment than men. This result is consistent with other research findings in different geographical contexts, such as Greece, the US, India, and Brazil, demonstrating that women care more about the environment than men and score higher on the NEP scale [17,[78][79][80][81]. This finding can be attributed to gender roles, societal expectations, and women's perceived responsibility for household and community well-being.…”
Section: Discussionsupporting
confidence: 91%
“…Some of the most well‐known examples of local community involvement in the design and choice of sustainable management practices include the regional natural parks in France, the National Park of Richtersveld in North Africa (Steenkamp & Hughes, ) and the national park of Nepal (Hough, ; Hough & Sherpa, ). Also, in many studies, the relationship between native peoples and special protected areas was explored (e.g., Halpern et al, ; Singleton, ; Mascia, Claus, & Naidoo, ; Visseren‐Hamakers, Leroy & Glasbergen, ; Ortega‐Álvarez, Sánchez‐González, Valera, & Berlanga, ; Christie et al, ; Halkos & Matsiori, ). On the other hand, there are many attempts to specify the role of people to environmental sustainability and protection (Scott, ; Wong & Wan, ; Strezov, Evans, & Evans, ; Gkargkavouzi, Halkos & Matsiori, ; Bosetti & Locatelli ; Gkargkavouzi, Paraskevopoulos & Matsiori, ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to Halkos et al (2019), results suggest WTP can be influenced by a respondent's knowledge of and familiarity with the resource. Further, Halkos and Matsiori (2018) note knowledge of and differentiating between such groups may help implement successful preservation strategies.…”
Section: Conculsions and Implicationsmentioning
confidence: 99%
“…Similar toHalkos et al (2019), results suggest WTP can be influenced by a respondent's knowledge of and familiarity with the resource. Further,Halkos and Matsiori (2018) note knowledge of and differentiating between such groups may help implement successful preservation strategies.Results suggest sustainable intelligence plays an important role in predicting WTP of GIAHS resources. A policy implication is that education programs to increase residents' sustainable intelligence may increase WTP for preservation of not only the Batdam but also other GIAHS.…”
mentioning
confidence: 99%